2013
DOI: 10.1371/journal.pone.0053655
|View full text |Cite
|
Sign up to set email alerts
|

NOS Inhibition Enhances Myogenic Tone by Increasing Rho-Kinase Mediated Ca2+ Sensitivity in the Male but Not the Female Gerbil Spiral Modiolar Artery

Abstract: Cochlear blood flow regulation is important to prevent hearing loss caused by ischemia and oxidative stress. Cochlear blood supply is provided by the spiral modiolar artery (SMA). The myogenic tone of the SMA is enhanced by the nitric oxide synthase (NOS) blocker L-NG-Nitro-Arginine (LNNA) in males, but not in females. Here, we investigated whether this gender difference is based on differences in the cytosolic Ca2+ concentration and/or the Ca2+ sensitivity of the myofilaments. Vascular diameter, myogenic tone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Both NO and ROS in VSMCs regulated RyR-mediated Ca 2ϩ mobilization (384, 1645), but by distinct signaling pathways (752,861,866,1224). NO dilated gracilis muscle arteries and afferent arterioles by activating MLCP (129, 1499,1503), and attenuated myogenic tone of nonrenal vessels by inhibiting Rho kinase in VSMCs (475,1214,1458). This may also occur in the renal microcirculation (1358).…”
Section: Nomentioning
confidence: 99%
“…Both NO and ROS in VSMCs regulated RyR-mediated Ca 2ϩ mobilization (384, 1645), but by distinct signaling pathways (752,861,866,1224). NO dilated gracilis muscle arteries and afferent arterioles by activating MLCP (129, 1499,1503), and attenuated myogenic tone of nonrenal vessels by inhibiting Rho kinase in VSMCs (475,1214,1458). This may also occur in the renal microcirculation (1358).…”
Section: Nomentioning
confidence: 99%
“…Stimulation of BK channel activity by the nitric oxide (NO)/soluble guanylate cyclase (sGC)/cGMP-dependent protein kinase (PKG) pathway, which is important in mediating the effects of endothelial-dependent vasodilators, is not thought to be involved in modulating the myogenic response of small resistance arteries during basal tone because there is no evidence for pressure-induced release of NO from the endothelium47. Under physiological conditions, PKG exists as a dimer and oxidants such H 2 O 2 promote the formation of a disulfide bond between appositioned cysteine residues (Cys 42 ) within PKG dimers8.…”
Section: Introductionmentioning
confidence: 99%
“…Such changes in Ca 2+ sensitivity further augment the Ca 2+ -dependent myogenic vasoconstrictions [3640]. We have previously shown that myogenic tone in the male, but not female, gerbil SMA is regulated not by changes in the SMC global Ca 2+ but by rho-kinase-mediated changes in the Ca 2+ sensitivity of contraction, which was revealed under inhibition of NO-mediated signaling [23]. The present study shows that the regulation of vascular tone in the female gerbil SMA is also determined by the Ca 2+ sensitivity of the myofilament, with the crucial difference that increase in intravascular pressure significantly lowered the Ca 2+ sensitivity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Data points for concentration curves were obtained by averaging diameter and fluorescence intensity measurements over the last 30s of each Ca 2+ step and normalizing against the average value obtained in PSS at 60 cmH 2 O. Data points from individual vessels were fitted to a modified Hill equation:where Dia is the normalized diameter, Max is the diameter at 60 cmH 2 O in PSS containing 1 mM Ca 2+ , Base is the maximum achievable constriction with respect to Max for the female gerbil SMA estimated from previous observations [23], [Ca 2+ ] is the normalized cytosolic Ca 2+ concentration, h is the slope coefficient, and FC 50 is the fold-change in the global cytosolic Ca 2+ concentration that is necessary for a half-maximal constriction. The slope coefficient h was set to -5.2 and Max was clamped to 100 %.…”
Section: Methodsmentioning
confidence: 99%